Análise da qualidade de gelatina obtida de tarsos de frango e aspectos envolvidos no processo produtivo - Almeida, Poliana Fernandes de (2012)
This study features gelatin production as a new possibility in the production chain of broilers, through the use of chicken by-products. Given the lack of other works on sensory analysis of gelatins made with collagen extracted from chicken feet, the objective of this study was to assess the acceptability of that gelatin by evaluating its sensory qualities through comparison with a leading market brand, as well as the viability of its production process. To that end, gelatin production consisted of a 22 experimental design, with 7 grape-flavored gelatin formulations made with collagen extracted from chicken feet, containing varying concentrations of sugar (7.10% to 28.6%) and collagen (35.7% to 71.4%). A 9-point hedonic scale was used to evaluate color, flavor, texture and aroma of the formulations by 50 untrained tasters. Optimization was done using surface response analysis, with sensory analysis results evaluated by test t Student using Statistica for Windows® and Windows Excel. A proximate composition analysis of chicken feet and their gelatin was carried out to identify nutritional qualities, and the yield of extracted collagen material was measured. The production process viability study was done through an industrial project for gelatin extraction. The results of the sensory analyses showed no significant differences among the samples at a 95% confidence level; the best gelatin was the formulation with the highest concentrations of sugar and collagen, and grape- and pineapple-flavored gelatins had the best acceptance by consumers. The results showed a 5.33% gelatin yield for chicken feet, and gelatin composition was 9.749, 4.807, 6.919 and 78.525 g/100g for moisture, ash, lipids and proteins, respectively. Mass spectrometry analysis of gelatin salts showed that their composition was 99.44% Na, Ca, K, Mg, P and S, all of which are highly important macro-minerals for human health. A cost analysis determined that gelatin production is feasible, indicating a sales profit level of 15%. This proposal of giving new uses for chicken feet, which are regarded as by-products in slaughterhouses, results in a competitive advantage both for the slaughterhouse (which gets a new income source and achieves greater sustainability) and the gelatin industry (for which innovative raw materials and new industrial processes allow greater competitiveness in the marketplace).